Monitoring and Automation System of Swiftlet House Using Internet Of Things (IoT) Based - Budi Usmanto; Novi Ayu Kristiana Dewi (Institut Bakti Nusantara, 2023)
This research aims to make a tool in the form of a technological engineering system that is integrated with its operation so that swiftlet farmers can use it. This research is expected to produce a more effective and efficient technology than partial tools and has not yet answered the needs of swallow farmers. The stages in this study used flowcharts consisting of literature studies, program design, making system blocks, system integration, tool testing, and analysis of the results. The system design consists of determining tools and materials and making a block diagram of the work system of the tool with the ESP32 microcontroller. In system settings, it is divided into several system blocks: sound control system block, temperature and humidity control, window opening and closing control, lighting control and streaming video monitoring in swiftlet houses. Based on the results of the study, it was obtained that monitoring and automation system tools for swallow houses use IoT-based Esp32. This tool can automatically regulate and automate sound, temperature, humidity, lighting, and windows in swiftlet houses and can be monitored remotely.